PERBANDINGAN REGRESI ROBUST PENDUGA MM DENGAN METODE RANDOM SAMPLE CONSENSUS DALAM MENANGANI PENCILAN - IRFAGUTAMI, NI PUTU NIA; SRINADI, I GUSTI AYU MADE; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 3 No 2 (2014)DO - 10.24843/MTK.2014.v03.i02.p065, 2014)
The presence of outliers in observation can result in biased in parameter estimation using ordinary least square ( OLS ). Robust regression MM-estimator is one of the estimations methods that able to obtain a robust estimator against outliers. Random sample consensus (ransac) is another method that can be used to construct a model for observations data and also estimating a robust estimator against outliers. Based on the study, ransac obtained model with less biased estimator than robust regression MM-estimator.
Keywords: Outlier, Robust Regression, MM-estimate, ransac